An Analytical Study of Translating some of Different Oath Formats in The Glorious Qur’an in The Parts of 28, 29 and 30. - Al-Burbar, Aya; Mohsen, Al-Hussein S.; Al-Zidiwi, Hajer (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The research evaluates variations in accuracy and interpretation across three different translations of the Holy Qur’an: Yusuf Ali’s (1934), Mohammed Marmaduke’s (1948), and Al Muntada alIslami Trust’s (2010). Focusing on some verses containing oaths in parts (28, 29, and 30), the study meticulously examines the type of oath used and its significance. Through subjective experiences, it aims to understand the specific meanings and behaviors conveyed in these verses, shedding light on differences in oath styles. The recommendation is to expand the study to encompass a broader examination of oath types throughout various sections of the Qur’an, extending beyond specific Surahs or hadiths. By including additional sources and texts, scholars can deepen their understanding of oath concepts within Islamic scripture. This research serves as a valuable resource, inspiring further exploration into the multifaceted nature of oaths in religious texts. The results cover parts 28, 29, and 30, comprising 57 Surahs, with 20 of them containing oath verses primarily aimed at strengthening faith. The researchers employed an inductive method to reveal the secrets of the Qur’an through the analysis of oath-related content and its translation in these parts.